Integrating health disaster risk management into urban resilience in Malaysia: barriers, practices and construct validation - Abdul Rahim, `Ainatul Fathiyah; Zen, Irina Safitri; Abdullah, Alias (IIUM Press, 2025)
The COVID-19 pandemic highlighted critical vulnerabilities in Malaysia's urban health systems and disaster risk management, particularly in responding to complex health emergencies in densely populated areas. This study examines barriers and current practices of Health Emergency and Disaster Risk Management (Health-EDRM) within the context of urban resilience. A quantitative survey was conducted among 179 practitioners across multiple agencies. Descriptive analysis identified key barriers, including overwhelmed healthcare capacity (M = 3.29, SD = 0.957), low public compliance (M = 3.20, SD = 0.925), and insufficient resource allocation (M = 3.13, SD = 0.985). Confirmatory factor analysis (CFA) was used to assess the reliability and validity of the key constructs. The validated constructs, such as governance, risk assessment, preparedness, capacity building, and recovery demonstrated strong internal consistency and sampling adequacy. These findings highlight systemic gaps in current practices and provide empirical evidence that existing Health-EDRM approaches remain insufficient to address the complexity of urban disasters. By validating these constructs, this study lays the groundwork for an integrated framework to guide policymakers and practitioners in strengthening governance, multisectoral collaboration, preparedness for future health emergencies.